Hospital management of suicidal behaviour and subsequent mortality: a prospective cohort study. (September 2015) - Kapur, Nav; Steeg, Sarah; Turnbull, Pauline; Webb, Roger; Bergen, Helen; Hawton, Keith; Geulayov, Galit; Townsend, Ellen; Ness, Jennifer; Waters, Keith; Cooper, Jayne
Summary Background Self-poisoning and self-injury are associated with a high risk of suicide or death from any cause but the effect of routine aspects of hospital management on mortality risk is unknown. Methods We did a prospective cohort study using data for adults who had self-harmed presenting to five emergency departments in the UK between 2000 and 2010. We assessed the relation between four aspects of management (psychosocial assessment, medical admission, psychiatric admission, referral for mental health follow-up) and death by suicide or any cause within 12 months of presentation. Findings Of 38 415 individuals presenting with self-harm, 261 (0·7%) died by suicide and 832 (2·2%) died from any cause within 12 months. Most aspects of management were associated with a higher mortality risk in unadjusted analyses. Psychiatric admission was associated with the highest risks for both suicide (hazard ratio 2·35, 95% CI 1·59–3·45) and all-cause mortality (2·35, 2·04–2·72). After adjustment for baseline variables, the hazard ratios were generally smaller, particularly for psychiatric admission. There were significant interactions by sex, age, and history of self-harm. Interpretation This was an observational study and so we cannot infer causation. However, our finding that clinical services seem to reserve the most intensive levels of treatment for patients at highest risk is reassuring. Aspects of routine management might be associated with a lower mortality risk but these effects vary by clinical subgroup. Funding UK Department of Health.